Determinant of Local Expenditure Quality Model and Relation with Local Development in East Java - Listiana, Yufita; Juanda, Bambang; Mulatsih, Sri (Universitas Muhammdaiyah Surakarta, 2016)
This research aim is to analyze local expenditure quality in East Java based on five construct variables. Each construct variables consist of 40 indicators. This research use secondary data is Local Government Management Evaluation Report each region in East Java. Data of local development use poverty, unemployment, Gini index, economic growth, GDP per capita, and Human Development Index. This research uses analysis Structural Equation Modeling. It uses to know appropriate indicators to improve spending quality. The result shows that from 40 indicators just there are 21 indicators which have reached criteria good expenditure quality. Effectively has influence to expenditure quality more than 50% to describe model variation in local expenditure quality. It means that East Java has high financial effectively in increase public service because quality expenditure increasing continuously each year.